2008
DOI: 10.1007/s00484-008-0157-4
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic climatology of the long-distance dispersal of white pine blister rust. I. Development of an upper level synoptic classification

Abstract: This study developed a methodology to temporally classify large scale, upper level atmospheric conditions over North America, utilizing a newly-developed upper level synoptic classification (ULSC). Four meteorological variables: geopotential height, specific humidity, and u- and v-wind components, at the 500 hPa level over North America were obtained from the NCEP/NCAR Reanalysis Project dataset for the period 1965-1974. These data were subjected to principal components analysis to standardize and reduce the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Although a flight from California is more than 1,200 km, the rust also appears to have completed other, somewhat shorter dispersals (Geils et al 2003), and longer distances for other rusts are reported (Nagarajan and Singh 1990). Source regions such as Oregon, Idaho and Wyoming cannot be ruled out; few, infrequent synoptic patterns (Frank et al 2008, this issue) would transport rusts from these locations to south-central New Mexico.…”
Section: Dispersal To the Sacramento Mountainsmentioning
confidence: 89%
See 1 more Smart Citation
“…Although a flight from California is more than 1,200 km, the rust also appears to have completed other, somewhat shorter dispersals (Geils et al 2003), and longer distances for other rusts are reported (Nagarajan and Singh 1990). Source regions such as Oregon, Idaho and Wyoming cannot be ruled out; few, infrequent synoptic patterns (Frank et al 2008, this issue) would transport rusts from these locations to south-central New Mexico.…”
Section: Dispersal To the Sacramento Mountainsmentioning
confidence: 89%
“…The patterns of upper level flow identified by the ULSC (Frank et al 2008, this issue) describe the potential connections between source and target locations. Although host and rust populations have patchy distributions at various landscape scales, they can be mapped at a county level using data from published literature, herbarium records, and field reports (Fig.…”
Section: Dispersal To the Sacramento Mountainsmentioning
confidence: 98%
“…Most long‐distance spread of WPBR likely occurs through movement of thick‐walled aeciospores, which are produced on pines and fairly resistant to desiccation and UV radiation (Frank, Geils et al., ; Kasanen, ; Zambino, ). Wind speed, wind direction, and local and regional climate and weather systems are integral forces that impact plant disease epidemics through their relationship with spore dispersal, but studies in complex mountain meteorology are difficult (Aylor, ; Frank, Kalkstein, Geils, & Thistle, ; Holdenrieder et al., ; Jacobi, Geils, & Taylor, ; Jacobi, Geils, Taylor, & Zentz, ; Mielke, ). Winds must move in the appropriate direction from the spore source to the host location, which can be challenging to model in the complex topography of the Rocky Mountains as observed in tree line communities of whitebark pine and with comandra blister rust ( Cronartium comandrae Pk.)…”
Section: Introductionmentioning
confidence: 99%
“…The current SSC was developed by Sheridan () and was referred to as “SSC2” because it stemmed from an extensive line of research initiated by Muller, Kalkstein, and others in the late 1970s (Kalkstein et al ; Lamb ; Muller ) that eventually led to an initial version that is sometimes referred to as “SSC1” (see Hondula et al for an in‐depth history). A combination of weather variables (air temperature, dew‐point depression, wind speed, mean cloud cover, mean sea‐level pressure, diurnal temperature range, and diurnal dew‐point range) 6is used to numerically characterize the state of the atmosphere; these quantities are subsequently differentiated into weather‐type categories, encompassing variables that synergistically affect human health (Davis et al ; Greene et al ) and various ecological systems (e.g., Frank et al ,).…”
Section: Introductionmentioning
confidence: 99%